Influence of Histidine on the contractility and adrenaline inotropic effect in the experiments with myocardium of right ventricular of Non pregnant and Pregnant Rats - Tsirkin, Victor; Nozdrachev, Alexander; Korotaeva, Julia; Khodyrev, Grigorij (Journal of Cardiology and Cardiovascular Medicine, 2018)
It was investigated contractility and adrenoreactivity of intact myocardium strips of right ventricular in experiment with 60 rats. They were assessed by the force of induce contraction and its changes under the influence of adrenaline (10-9 or 10-5 g / ml). Found that these indicators do not depend on the phases of the estrous cycle and the presence of pregnancy. Histidine (10-10-10-4 g / ml) did not increase the response to adrenalin (10-9 g / ml), but increased the force of the contractions in rats in progesterone dominance (trend) and pregnancy (statistically significant). Against the background of propranolol (10-8 g / mL) or atenolol (10-8, 10-6 g / mL), adrenaline (10-5 g / mL) instead of increasing the force of contraction reduced it (probably due to activation of beta3-, alpha1 - and alpha1 a2- adrenergic receptors), and histidine (10-4 g / mL) prevented this reduction, but does not restore full ability of adrenaline to exert a positive inotropic effect. On the background of nicergoline (10-8 g / mL or nicergoline and propranolol (10-8 g / mL), adrenaline (10-5 g / mL) did not alter the force of contraction, and histidine (10-4 g/mL) restore ability of adrenaline to exert a positive inotropic effect but only in the experiments with nicergoline. Concluded that histidine increases the efficiency of the activation of all three (beta1-, beta2- and beta3-) populations of myocardial beta-adrenoceptoprs, including at lower by adrenergic blockers. Therefore, histidine proposed as an antagonist of beta-adrenergic blockers and as resensitizator of these receptors. Core Tip: In the experiments with strips of the right ventricle of 40 nonpregnant and 20 pregnant rats histidine (10-10-10-4 g /mL) did not increase the response to adrenaline (10-9 g / ml), but increased the force of contractions in pregnant rats. On the background of propranolol (10-8 g / mL) or atenolol (10-8, 10-6 g / mL), adrenaline (10-5g/mL) showed a negative inotropic effect, and histidine (10-4 g / mL) prevented it, but does not restore the ability of adrenaline to show positive inotropic effect,. i.e histidine exhibits the properties of the antagonist of beta-blockers and of resensitizator of beta-adrenoceptors